Application de la carte interculturelle en tant que média d’apprentissage interculturel indonésien-français sur la compréhension écrite des lycéens de l’hospitalité XI SMK Negeri 3 Magelang - Taffitia Risnanti Yusuf; Sri Handayani (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
This study is motivated by one of the objectives of French language subjects in high school within the independent curriculum, specifically regarding cross-cultural understanding. However, this goal has not been fully met at SMK N 3 Magelang because cross-cultural learning is only inserted during the lesson. The purpose of this study was to determine the learning outcomes and knowledge of students after using the Indonesian French cross-cultural quartet media in reading skills. This research employs an experimental case study design with 30 respondents from SMK N 3 Magelang. The methods used to collect data were tests and documentation. The test consisted of 20 multiple-choice questions. The results of this study indicate that the application of cross-cultural quartet media in class XI Hospitality students has a good effect. This can be seen from the overall percentage of students passing the Indonesian French cross-cultural knowledge test, which is as high as 90%, with an average score of 82.83 obtained by students. It can be concluded that the application of cross-cultural quartet media yields good learning outcomes and enhances the cross-cultural knowledge of Indonesian French in reading skills among XI Hospitality students of SMK N 3 Magelang after the media is accepted.